1993
DOI: 10.1021/j100111a031
|View full text |Cite
|
Sign up to set email alerts
|

Chemical reaction initiation and hot-spot formation in shocked energetic molecular materials

Abstract: A theoretical model is developed to describe the nature of molecular energy transfer and chemical reactivity in shocked energetic materials. The intent is to develop a fundamental understanding of the sensitivity of secondary explosives, which are solids consisting of large organic molecules. Because secondary explosives are stable molecules with large barriers to chemical reaction, before reactions can occur, a sizable amount of energy must be transferred from the shock produced phonons to the molecules' inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
187
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(190 citation statements)
references
References 24 publications
2
187
0
1
Order By: Relevance
“…To clarify this, a theoretical estimation of the number of doorway modes for explosives has been carried out by Tokmakoff et al [63] based on the theory of Dlott and Fayer. It has been suggested that the energy transfer rate is proportional to the number of normal mode vibrations.…”
Section: Energy Transfer Rate Methodsmentioning
confidence: 99%
“…To clarify this, a theoretical estimation of the number of doorway modes for explosives has been carried out by Tokmakoff et al [63] based on the theory of Dlott and Fayer. It has been suggested that the energy transfer rate is proportional to the number of normal mode vibrations.…”
Section: Energy Transfer Rate Methodsmentioning
confidence: 99%
“…The specific pathway by which the mechanical energy of the shockwave funnels into a molecular excitation, whether vibrational or electronic, is a current topic of debate. [1][2][3][4][5][6][7][8][9][10] The goal of this research is to provide an unambiguous determination of the Raman-active vibrations for cyclotrimethylene trinitramine ͑RDX͒, a common secondary explosive. Secondary explosives are advantageous to study because they are relatively insensitive to mechanical initiation compared to primary explosives.…”
Section: Introductionmentioning
confidence: 99%
“…For secondary explosives, it has been proposed that low-energy molecular vibrations, termed "doorway modes," are critical to detonation initiation. [5][6][7] These necessarily anharmonic vibrations provide the bridge between the shock-populated phonons of the material and the "uppumping" process through which the upper vibrational states of the molecule are increasingly populated to the point of decomposition. However, before a theory involving a complicated manifold of anharmonic vibrational interactions can be substantiated, the static vibrational properties of secondary explosives must first be experimentally well defined.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Shock compression of an energetic material is well characterized by translational overheating ͑phonon quasitemperature͒. In a model proposed by Dlott and Fayer, 3 it is assumed that there is continuous energy flow from the compressively heated phonon bath into vibrational doorway modes mediated by a multiphonon up-pumping mechanism that heats the molecules to temperatures at which chemical bonds break. This mechanism requires times of the order of hundreds of picoseconds for a ladder of vibrational states to be climbed and to reach vibrational thermal equilibrium.…”
Section: Introductionmentioning
confidence: 99%